2010
DOI: 10.1007/s00775-010-0675-5
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of concentrations of selected trace elements with Gleason grade of prostate tissues

Abstract: The causes of prostate cancer are still obscure but some evidence indicates that there is a close connection between several trace elements and processes which may lead to malignant cells. In our study the microbeam synchrotron radiation X-ray fluorescence emission (micro-SRIXE) technique was applied for quantitative analysis of selected elements. For the first time, we correlate the concentrations of Mn, Fe, Cu, and Zn with the clinical stage of the prostate cancer at the time of operation (described by Gleas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…Decreased serum Mn concentrations were reported in patients with bladder and renal cancers Pirincci et al;. It was shown that decreased Mn is potentially associated with decreased activity of superoxide dismutase in advanced stages of cancer (Gleason grade 3 or 4) when compared to group with Gleason 2 grade disease (Banas et al, 2010). In our study, we think that significant decrease in Mn levels compared controls is due to the fact that majority of the patients included had advanced disease.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Decreased serum Mn concentrations were reported in patients with bladder and renal cancers Pirincci et al;. It was shown that decreased Mn is potentially associated with decreased activity of superoxide dismutase in advanced stages of cancer (Gleason grade 3 or 4) when compared to group with Gleason 2 grade disease (Banas et al, 2010). In our study, we think that significant decrease in Mn levels compared controls is due to the fact that majority of the patients included had advanced disease.…”
Section: Discussionsupporting
confidence: 48%
“…Thus, toxicity/duality contradiction in trace elements leads the biological system to develop ability to recognize and deliver metal compounds to its target without enabling them to involve in toxic reactions Sayır et al, 2011). It has been proven that some trace elements have major role in cancer biology; however, there is still a gap in our understanding regarding relationship between trace elements functions and initiation, advancement and inhibition of carcinogenic process in prostatic gland (Geraki et al, 2002;Naga Raju et al, 2006;Guntupalli et al, 2007;Banas et al, 2010). Thus, there is a need for trace element analysis in human tissues with or without cancer that can show relationship between cancer and these elements.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, isolated studies have reported a significantly higher tissue level of zinc in PCa as compared to BPH [12] and normal prostatic tissue [27] or an insignificantly lower level of zinc level in PCa as compared to normal prostatic tissue [28]. There are conflicting reports about tissue zinc levels in BPH as well; some found a decrease [17] while others an increase [13] or no change [18,26] as compared to normal prostatic tissue.…”
Section: Discussionmentioning
confidence: 98%
“…Copper plays an important role in the carcinogenic process that may be also linked with its ability to bind to some proteins and thus to acquire the angiogenic activity. On the other hand, copper mediates the involvement of cellular proliferation via the activation of angiogenic growth factors (Banas et al, 2010). Additionally, because copper is expected to initiate angiogenesis, elevated concentration of this element is likely to promote prostate cancer by increasing the blood supply for tumour growth.…”
Section: Discussionmentioning
confidence: 99%